Pesinden Maria Magdalena Rubinem dalam Upaya Pelestarian Kesenian Tradisi Karawitan di Yogyakarta (1943-2014) (DIAKRONIK: Jurnal Pemikiran dan Penelitian Sejarah, 2025)
This article examines the pivotal role of Maria Magdalena Rubinem, a renowned sinden from Yogyakarta, in the preservation of Javanese traditional music (karawitan) from 1943 to 2014. Amidst the declining popularity of sinden and traditional performances in modern times, Rubinem’s dedication has been instrumental in sustaining and transmitting cultural heritage. The study employs metode sejarah, including heuristik, kritik sumber, interpretasi, and historiografi, with data sourced from archives, literature, and structured interviews. The findings highlight Rubinem’s significant contributions to the continuity of karawitan and her recognition as an influential figure in Indonesian traditional arts.